Samuel Tucker correspondence - Tucker, Samuel, active 1783.
ALS written by Tucker in Trenton, N.J., to Elizabeth Lawrence, of Philadelphia, Pa., concerning rents owed to her.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lawrence, Elizabeth, -- active 1783. -- Correspondence; Rent; New Jersey -- History -- Revolution, 1775-1783.; Pennsylvania -- History -- Revolution, 1775-1783.; Philadelphia (Pa.) -- History -- Revolution, 1775-1783.; Trenton (N.J.) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.